CORPORATE CRIMINAL LIABILITY IN INDONESIA - Pramugara Wirawan; Rinta Nanda (DUTA BANGSA UNIVERSITY INDONESIA, 2021)
The lack of handling corporate corruption, while the involvement of private corporations in many corruption cases in Indonesia is very massive, cannot be separated from legal construction so far based on criminal liability that tends to judge the individuals’ fault. By applying agency theory and based on a normative juridical approach by inventorying adequate legal materials, two main conclusions are generated. First, criminal liability of corporate corruption has fulfilled the aspects of philosophical and sociological juridical, as the purpose of criminal law in society is to fulfill a sense of justice for the occurrence of social symptoms in the corporation. Second, the reconstruction of criminal liability against corporate corruption must be carried out within the framework of reforming the formation of corruption criminal law in the future through the application of non-fault liability. In connection with the criminal act of corruption which is related to the recovery of state/regional financial losses and considering the corporate criminal liability model that impacts on public benefit, as well as legal certainty and justice, it is necessary to renew corruption law which confirms the notion of corruption and formulate the criteria of piercing the corporate veil, strict liability, vicarious liability, and secondary liability.